The effect of branding on consumer purchase intention: a study in Turkish apparel industry - Demir, Şule (My University, 2008)
MARKANIN TÜKETİCİ SATIN ALMA NİYETİNE ETKİSİ: TÜRKIYE GİYİM SEKTÖRÜ ÜZERİNDE BİR ARAŞTIRMA Bu çalısma, Türkiye hazır giyim sektöründeki marka çagrısımları ve marka ögeleri ile satın alma niyeti arasındaki iliskileri incelemektedir. Bu amaçla, marka çagrısımları ve marka ögelerinin 1980 – 1990 yılları arasında dogan gençlerin satın alma niyeti ile iliskileri ortaya konulmustur. Çalısmanın çerçevesini belirlemeden önce Türkiye hazır giyim sektörünün durumu ve 1980 – 1990 arasında dogan gençlerin egilimlerini saptayabilmek amacıyla literature arastırması yapılmıstır. Arastırma sonuçlarına göre marka bilinirligi, marka sadakati, algılanan ürün kalitesi, fiyat bilinci ve moda bilinci’nin tüketicilerin alım niyetinde etkili karar degiskenleri oldugu saptanmıstır. Bu degiskenler incelendiginde ise marka bilinirligi, marka sadakati, algılanan ürün kalitesi ve fiyat bilincinin marka degeri kavramı ile iliskili oldugu görülmüstür. Çıkan bu sonuç üzerine günümüzün en önemli konularından biri olan marka degerine odaklanılmasına karar verilmistir. Çalısmanın çerçevesi olusturulurken ise Aaker (1991) ve Keller (1993, 1998)’ın marka degeri modelleri dikkate alınmıstır. Çalısmanın ana çatısını ise Keller (1993, 1998)’ın marka degeri modelleri olusturmaktadır. Gelistirilen model dogrultusunda marka çagrısımları ve marka ögeleri ile satın alma niyeti arasındaki iliskiler test edilerek incelenmis ve iliskilerin varlıgı saptanmıstır.

THE EFFECT OF BRANDING ON CONSUMER PURCHASE INTENTION: A STUDY IN TURKISH APPAREL INDUSTRY This study focuses on the effects of the brand strategies on consumer purchase intention in the field of apparel marketing. For this purpose, it is aimed to state the relations in between brand associations and brand elements with the purchase intention of the generation born between 1980 and 1990. Before designed the study, a literature review, was conducted in order to analyze the textile and apparel industry and preferences of Generation born between 1980 and 1990 through apparel industry. The results shows that brand awareness, brand loyalty, perceived clothing quality, price consciousness, fashion consciousness are the decision variables, effective on consumers’ purchase intention (Sproles&Kendall,1986; Fairhurst,1985; Abraham,1992; Chung,1999; Sung,1998). When analyzed these variables, it is seen that four of them, which are brand awareness, brand loyalty, perceived quality, and price consciousness, are directly relating with the concept of brand equity. And it is decided to focus brand equity, that is one of the hottest topics in management today. While shaping the research frame, Aaker and Keller’s models are basically taken into consideration and analyzed and the Keller’s model is used while creating the conceptual framework of the study. Based on the framework the relations were tested and the whole relations between brand associations and brand elements with purchase intention were stated through the research results. iii TABLE OF CONTENTS Page Number LIST OF TABLES……………………………………………………………………..ix LIST OF FIGURES……………………………………………………………………xi INTRODUCTION….…………………………………………………………………..1 1. BRAND CONCEPT 1.1. Definitions of Brand…………………………………………………………….8 1.2. Importance of Branding…………………………………………………………9 1.3. Consumer – Brand Relationships…………………………………………….. 16 2. BRAND EQUITY CONCEPT 2.1. Definitions of Brand Equity…………………………………………………...24 2.2. Brand Equity Research………………………………………………………...27 2.3. Drivers of Brand Knowledge………………………………………………….37 2.3.1. Brand Awareness……………………………………………………….38 2.3.2. Brand Associations……………………………………………………..41 2.3.2.1.Attributes…………………………………………………………...51 2.3.2.1.1. Product Related Attributes………………………………….52 2.3.2.1.2. Non- Product Related Attributes…………………………...52 2.3.2.2.Benefits……………………………………………………………..55 2.3.2.2.1. Functional Benefits…………………………………………57 2.3.2.2.2. Experiential Benefit………………………………………...58 2.3.2.2.3. Symbolic Benefits…………………………………………..58 2.3.2.3.Secondary Associations…………………………………………….60 2.4. Branding Elements to Create Brand Associations…………………………….62 2.4.1. Brand Name…………………………………………………………….63 2.4.2. Packaging…………………………………………………………….....64 2.4.3. Logos and Symbols………………………………………………….…66 2.4.4. Slogans……………………………………………………………..…...68 2.4.5. Jingles……………………………………………………………..........68 2.4.6. Characters………………………………………………………………68 3. BRAND ATTITUDE 3.1. Definitions of Brand Attitude…………………………………………………69 3.2. Relationship Between Brand Associations & Elements with Brand Attitude…74 4. BACKGROUND OF THE STUDY 4.1. Textile Industry……………………………………………………………......77 4.2. Ready – to – Wear Industry……………………………………………………79 iv 4.3. The Market Overview for Ready to Wear Industry in Turkey………………...82 4.4. The Overview about the Generation, born between 1980 and 1990…………..87 5. RESEARCH DESIGN PROCESS METHODOLOGY 5.1. Objective / significant of study………………………………………………...95 5.2. Hypothesis……………………………………………………………..............96 5.3.Variables……………………………………………………………..................98 5.4. Data Collection Procedure, Instrument and Design………………………….100 5.5.Sampling……………………………………………………………................101 5.6. Measurement and Scales……………………………………………………..102 5.6.1 Frequency Distribution………………………………………………..102 5.6.2 Cross Tabulation………………………………………………………102 5.6.3 Validity and Reliability………………………………………………..103 5.6.4 Multiple Regression…………………………………...........................104 5.6.5 T-Test and Anova……………………………………..........................104 6. RESEARCH DESIGN 6.1. Instruments……………………………………………………………...........106 6.2. Sampling and Method………………………………………………………..106 6.3. Research Findings…………………………………………………………...110 6.3.1. Factor Analysis………………………………………………………..110 6.3.2. Regression Analysis…………………………………………………..114 6.3.3. Independent Sample T – Test…………….…………………………...121 6.3.4. ANOVA………………………………….…………………………... 123 7. CONCLUSIONS, IMPLICATIONS AND RECOMMENDATIONS 7.1. Conclusion and Discussions………………………………………………….125 7.2. Implications…………………………………………………………………..129 7.3. Limitations……………………………………………………………………133 7.4. Recommendations for Future Research……………………………………...134 APPENDIX 1…………………………………………………………………………135 APPENDIX 2…………………………………………………………………………141 REFERENCES………………………………………………………………………145
Keywords: Marka Degeri; Marka Öğeleri; Pazarlama; Satın Alma; Tüketici Davranışı; Üretim Yönetimi